All Days 1992
DOI: 10.4043/6949-ms
|View full text |Cite
|
Sign up to set email alerts
|

Hydromechanically Coupled Motions of a Crane Vessel and a Transport Barge

Abstract: Present day offshore lift operations feature the lifting of substantial loads horn a transport barge by means of large capacity semi submersible crane vessels with stem mounted dual cranes. During such operations the transport barge is moored perpendicular to the stem of the crane vessel. The motional behaviour of the crane vessel and transport barge are affected by hydro-mechanical coupling effects arising either from the hydrodynamic interaction between the two nearby vessels, or from mechanical coupling via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The simulation result showed that the lifted objects, which account for about 5% of the ship's weight, have a significant effect on the ship's motion. Baar et al 6) have calculated the dynamic response between the crane vessel and transport barge during offshore lifting due to hydrodynamic interaction effects. The results of the numerical model using the coupling equation stated that the hoisting wire and slings cause the effect of mechanical coupling on the vessel response.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation result showed that the lifted objects, which account for about 5% of the ship's weight, have a significant effect on the ship's motion. Baar et al 6) have calculated the dynamic response between the crane vessel and transport barge during offshore lifting due to hydrodynamic interaction effects. The results of the numerical model using the coupling equation stated that the hoisting wire and slings cause the effect of mechanical coupling on the vessel response.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction should be properly included if the two structures are in close vicinity, e.g., the hydrodynamic interaction between a transport barge and a floating crane vessel during lift-off operations (Mukerji, 1988;van den Boom et al, 1990;Baar et al, 1992). These studies showed that the hydrodynamic interaction had little effect on the responses of the crane tip, but affected the responses of the transport barge because of the small dimension of the barge compared with the crane vessel (Baar et al, 1992). In this case, the hydrodynamic interaction is expected to affect the responses of the MP greatly.…”
Section: Multi-body Hydrodynamics Using Potential Theorymentioning
confidence: 99%
“…The studies found that the hydrodynamic interaction had little effect on the responses of the crane tip, but affected the responses of the transport barge and thus greatly affected the lifting operations because of the small dimension of the barge compared with that of the crane vessel (Baar et al, 1992). The sheltering effects from columns and caissons of a gravity-based substructure (GBS) on the barge during a float-over installation were studied (Sun et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have been performed to investigate the heavy lifting operations in the oil and gas industry considering shielding effects, such as the lifting of a heavy load from a transport barge using a large capacity semi-submersible crane vessel (Mukerji, 1988;van den Boom et al, 1990;Baar et al, 1992). The studies found that the hydrodynamic interaction had little effect on the responses of the crane tip, but affected the responses of the transport barge and thus greatly affected the lifting operations because of the small dimension of the barge compared with that of the crane vessel (Baar et al, 1992).…”
Section: Introductionmentioning
confidence: 99%